Penyuluhan Internet Sehat Dan Aman Untuk Masyarakat Kelurahan Sentang, Kecamatan Kisaran Timur, Kabupaten Asahan - Khairul Saleh; Muhammad Akbar Syahbana Pane; Novialdi Ashari; Andi Prayogi (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2025)
This community service program aims to improve digital literacy among residents of Sentang Urban Village, Kisaran Timur Subdistrict, Asahan Regency. The main issues addressed include low public awareness of safe and healthy internet usage and the risks of data misuse, hoaxes, and cyberbullying. A participatory counseling method was employed, involving residents directly in discussions, simulations, and digital security practices. The results show a significant increase in participants’ understanding of digital ethics, cybersecurity, and wise internet usage. Additionally, the activity led to the formation of a new social institution called the Internet Safety Awareness Group (KWSIS), which serves as a community-based educational forum. These findings indicate that participatory approaches are effective in fostering digital literacy-based social change.